Analysis of the relationship between the exchange rate and stock market indicators: Evidence from Iraq - Al-Shimari, Kamal K. Jawad; Reda, Riyad Rahim; Hammood, Qasim Mohammed (Technium Social Sciences Journal, 2022)
The research seeks to identify the impact of exchange rate fluctuations on the most prominent indicators of the Iraqi stock market, such as market value and trading volume in the market, as these variables affect the activity of various productive institutions by providing the necessary funding to carry out new investment projects or sustain ongoing projects, as well as the possibility of confusing their plans and disrupting the achievement of their set goals in the event of inability to provide the necessary funding. The research studied the theoretical aspect of the exchange rate in general and in Iraq in particular, and the market value and volume of trading in the financial markets and the Iraq stock exchange. As for the analytical side, it relied on the annual data of the exchange rate, which is issued in the form of periodic bulletins by the Central Bank of Iraq, and the market value index and trading volume in the Iraqi Stock Exchange in Iraq for the period 2009-2019. The research reached a set of conclusions, the most prominent of which is that there is a long-term two-way reciprocal relationship between the exchange rate and the indicators of the mentioned financial markets in Iraq, despite the existence of an imbalance in the short time, the research also found that there is a possibility to consider the market value and trading volume indicators as general indicators about the direction of future economic activity in any national economy.